Application of S-100 absorbable hemostatic patch in endonasal endoscopic dacryocystorhinostomy: A randomized controlled trial - Hai-Sheng Zheng; Xing-Wu Zhong; Jia-Yao Xu; Hai-Yan Chen; Li-Na Liu; Bo-Wen Ou-Yang (Indian Journal of Ophthalmology)
Purpose: To investigate the effect of S-100 absorbable hemostatic patch coverage on anastomotic mucosa in endonasal endoscopic dacryocystorhinostomy (En-DCR). Methods: Two hundred and twenty-six patients with unilateral chronic dacryocystitis (CD) were randomly divided into two groups in a randomized controlled trial: the S-100 absorbable hemostatic patch group (group A) and the control group (group B). All patients underwent En-DCR. Group A received an S-100 absorbable hemostatic patch covering the wound approximately 2 mm around the ostium at the end of the En-DCR, whereas group B received no treatment. The patients were followed up for 12 months, and the mucosal epithelialization of the wound, granulation formation, bleeding, and success rate of ostial patency were compared between the two groups. Results: Our study included 106 patients in group A and 102 patients in group B. After 2 weeks, the intact mucosal epithelium lining the ostia was 96 in group A and 77 in group B. At 12 months follow-up, there were five patients with scars (4.7%) and seven patients with granulomas (6.6%) in group A, compared with 17 patients with scars (16.7%) and 18 patients with granulomas (17.6%) in group B. There were significant differences in scar formation and granuloma formation between the two groups (P = 0.007 and 0.007, respectively). The success rate of anastomotic patency was 92.5% (98/106) in group A and 78.4% (80/102) in group B (P < 0.05). Postoperative bleeding was more substantial in group B than in group A (P < 0.05). Conclusion: S-100 absorbable hemostatic patch cover can reduce the risk of postoperative bleeding and improve the success rate of EN-DCR treatment of CD by promoting healing of the anastomotic mucosa and preventing wound scar and granuloma formation after EN-DCR.